2020
DOI: 10.9770/jesi.2020.8.1(53)
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the role of environmental concern and the unified theory of acceptance and use of technology on working from home technologies adoption during COVID-19

Abstract: Working From Home (WFH) technologies has been used and discussed for a long time. The many positive benefits of WFH technologies, including its potential to create a more sustainable work activity, attracted many studies to gain a better understanding of this subject. This study is interested to understand the different factors, including environmental, influencing WFH technologies acceptance in this current shifting situation stimulated by the Covid-19 pandemic. An extended Unified Theory of Acceptance and Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…From the literature review, we have found that PE, EE, SI, and FC have a positive relationship with the use of e-government [8,45]. Additionally, one recent study also confirmed that PE, EE, SI, and FC have a positive influence on users' intention to use working from home technologies during the COVID-19 pandemic [46]. If citizens can use e-government and perceive that this website is useful, they will most likely adopt it.…”
Section: Discussionmentioning
confidence: 72%
“…From the literature review, we have found that PE, EE, SI, and FC have a positive relationship with the use of e-government [8,45]. Additionally, one recent study also confirmed that PE, EE, SI, and FC have a positive influence on users' intention to use working from home technologies during the COVID-19 pandemic [46]. If citizens can use e-government and perceive that this website is useful, they will most likely adopt it.…”
Section: Discussionmentioning
confidence: 72%
“…Factors influencing the acceptance of work from home (WFH) technologies in the period of COVID-19 was studied in [48] using the extended UTAUT model and employing environmental concern and 57.4% acceptance was predicted for WFH technology. In [49] , the adoption of digital contact tracing in the period of COVID-19 was studied.…”
Section: Literature Reviewmentioning
confidence: 99%
“…PU and PEOU are expected to be fairly general determinants of user technology acceptance [24]. Over the past few decades, psychologists and IS researchers have replicated Davis' study [25] to contribute empirical evidence on the association between PU, PEOU, and actual use [24,61,62,64]; however, investigating the direct effects of these two particular user beliefs on technology acceptance behavior, specifically during remote working, is a different approach which few studies have used (e.g., [65][66][67]). Consistent with extant research, we argue that when employees work from home due to the COVID-19 pandemic, their perceptions of using new technology will influence their decision to use it.…”
Section: Technology Acceptance: Antecedents and Work Engagementmentioning
confidence: 99%